2004
DOI: 10.1160/th03-08-0546
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen activator inhibitor-type 1: its plasma determinants and relation with cardiovascular risk

Abstract: The habitual level of PAI-1 is influenced by many factors, of which obesity and insulin resistance are the most important. It is possible to reduce plasma PAI-1 by changes in life style, e.g. weight reduction and physical activity. Data on potential interactions between environmental and metabolic variables on one hand, and the 4G/5G-polymorphism on the other hand, are still scarce. It becomes more and more clear that PAI-1 may possibly not be a major (causal) factor in cardiovascular disease, but its role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
2
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(112 citation statements)
references
References 177 publications
(159 reference statements)
7
100
2
3
Order By: Relevance
“…In particular, PAI-1 contributes to the determination ofoverall fibrinolytic activity [3] Reportedly, patients with type 2 diabetes mellitus have elevated blood PAI-1 levels and are prone to thrombosis; therefore, a relationship exists between elevated PAI-1 levels, arteriosclerosis, and cardiovascular disease onset [3]. Elevated blood PAI-1levels are caused by tumor necrosis factor-α (TNF-α), oxidative stress, and low-density lipoprotein-type hyperlipoproteinemia andare correlated with insulin resistance, triacylglycerol levels, and very low-density lipoprotein levels [2,[5][6][7]. Thecontrol of these factors is thought to play an important rolein the maintenance of low blood PAI-1 levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, PAI-1 contributes to the determination ofoverall fibrinolytic activity [3] Reportedly, patients with type 2 diabetes mellitus have elevated blood PAI-1 levels and are prone to thrombosis; therefore, a relationship exists between elevated PAI-1 levels, arteriosclerosis, and cardiovascular disease onset [3]. Elevated blood PAI-1levels are caused by tumor necrosis factor-α (TNF-α), oxidative stress, and low-density lipoprotein-type hyperlipoproteinemia andare correlated with insulin resistance, triacylglycerol levels, and very low-density lipoprotein levels [2,[5][6][7]. Thecontrol of these factors is thought to play an important rolein the maintenance of low blood PAI-1 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in patients with type 2 diabetes mellitus,an important treatment goal is the prevention of cardiovascular disease. These patients are also prone to thrombosis, and plasminogen activator inhibitor-1 (PAI-1) levels, which determine fibrinolytic activity in the fibrinolytic system, are considered informative [2]. A previous studyhas reported that elevated blood PAI-1 levels are associated with arteriosclerosis and cardiovascular disease onset [3].…”
Section: Introductionmentioning
confidence: 99%
“…The polymorphism is located in the gene promoter region (chromosome 7) and results in allele-specific responses to multiple agents. Accordingly, studies have shown the 4G allele to be associated with both higher levels of PAI-1 and cardiovascular risk [8].…”
Section: Polymorphisms and Genetic Analysismentioning
confidence: 99%
“…PAI-1 levels are positively correlated with the serum triglyceride levels and hypertension . However, some changes in life style, such as weight reduction and increased physical activity, can decrease plasma PAI-1 activity in affected individuals (Hoekstra, Geleijnse et al 2004).…”
Section: Pai-1 Over Expression In Diseasementioning
confidence: 99%